Optoelectronic and spectroscopic characterization of vapour-transport grown Cu2ZnSnS4 single crystals - Ng, Tat Ming; Weller, Mark T.; Kissling, Gabriela P.; Peter, Laurence M.; Dale, Philip; Babbe, Finn; De Wild, Jessica; Wenger, Bernard; Snaith, Henry; Lane, David W. (Royal Society of Chemistry, 2017)
Single crystals of Cu2ZnSnS4 (CZTS) have been grown by iodine vapor transport with and without addition of NaI. Crystals with tin-rich copper-poor and with zinc-rich copper-poor stoichiometries were obtained. The crystals were characterized by single crystal X-ray diffraction, energy-dispersive X-ray spectroscopy, photocurrent spectroscopy and electroreflectance spectroscopy using electrolyte contacts as well as by spectroscopic ellipsometry, Raman spectroscopy and photoluminescence spectroscopy (PL)/decay. Near-resonance Raman spectra indicate that the CZTS crystals adopt the kesterite structure with near-equilibrium residual disorder. The corrected external quantum efficiency of the p-type crystals measured by photocurrent spectroscopy approaches 100% close to the bandgap energy, indicating efficient carrier collection. The bandgap of the CZTS crystals estimated from the external quantum efficiency spectrum measured using an electrolyte contact was found to be 1.64–1.68 eV. An additional sub-bandgap photocurrent response (Urbach tail) was attributed to sub bandgap defect states. The room temperature PL of the crystals was attributed to radiative recombination via tail states, with lifetimes in the nanosecond range. At high excitation intensities, the PL spectrum also showed evidence of direct band to band transitions at ∼1.6 eV with a shorter decay time. Electrolyte electroreflectance spectra and spectra of the third derivative of the optical dielectric constant in the bandgap region were fitted to two optical transitions at 1.71 and 1.81 eV suggesting a larger valence band splitting than predicted theoretically. The high values of the EER broadening parameters (192 meV) indicate residual disorder consistent with the existence of tail states.